Gerakan Literasi Digital di Surakarta: (Studi Pada Dinas Komunikasi, Informatika, Statistik dan Persandian Surakarta) - Rasuli Rasuli; Zainul Abas (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
Internet user penetration is increasing in social life, the internet has become an integral part of society so that all activities of community life cannot be separated from its existence. There are still many users who do not fully understand the consequences of using the internet. Even though they have mastered how to use it, there are still many who use it not productively or safety. The application of digital literacy is considered to be a solution to various problems that occur in society due to the development of the internet and digital media. In this case, the government comes with its role to create a digital literate society and use the internet safely. This study intends to describe the digital literacy carried out by the Surakarta Communication, Informatics, Statistics and Encoding Office in an effort to create a society use the internet safely. This study used a qualitative descriptive approach with data collection techniques through interviews, observation and documentation. The subject of this research is the Office of Communication, Informatics, Statistics and Encoding Surakarta. The informants in this study were 4 people consisting of the Head of Communication and Encoding, the Department of Computer Administration for the Diskominfo SP Surakarta and 2 residents of the city of Surakarta. The results of this study indicate that the digital literacy program implemented by Diskominfo SP Surakarta as an effort to realize the community using the internet safely is carried out by means of socialization both face-to-face and through publication media and the implementation of digital transformation of information or public services. Digital literacy is carried out in stages, the first level is digital competence, the second is digital use (digital usage) and the third is digital transformation. Through this literacy level, the people of Surakarta can now use the internet safely.